The Role of Technology and Its Impact on Contemporary Islamic Education: Developments and Challenges - Azwar Rahmat (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The integration of technology into the learning process is expected to have a positive impact on both educators and students, making learning more engaging and increasing students’ motivation. However, successful implementation requires readiness from both teachers and students. Objective: This study aims to explore the role and application of technology in Islamic Religious Education and its effectiveness in improving teaching and learning processes. Method: The research employs Library Research (literature study) to collect and analyze information on technological developments in Islamic Religious Education. Relevant literature, studies, and guidelines were reviewed to understand how technology can be integrated in accordance with Islamic principles. Results: Technology in Islamic Religious Education serves as a tool, learning resource, and media to support teachers in innovating their teaching methods. Practical applications and media identified include TikTok, Instagram, Microsoft PowerPoint, and YouTube, all of which can enhance learning while adhering to the guidance of the Qur’an and Hadith. Conclusion: Technology plays a crucial role in modernizing Islamic education, enhancing student engagement, and improving the quality of learning. Contribution: This study provides educators with guideline-compliant strategies for integrating technology effectively in Islamic Religious Education, fostering active and innovative teaching practices.